Method for treating organic wastewater by using composite material constructed by waste lithium iron phosphate to activate peroxymonosulfate

By combining waste lithium iron phosphate with molybdenum disulfide to form iron-molybdenum bimetallic catalyst material, the problem of low conversion of Fe(II) and Fe(III) is solved, the activation efficiency of PMS and the removal effect of organic pollutants is significantly improved, and efficient organic wastewater treatment is achieved.

CN119612741APending Publication Date: 2025-03-14SHANGHAI SECOND POLYTECHNIC UNIVERSITY

Patent Information

Application Number
CN202411662605.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-20
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

In the prior art, the conversion rates of Fe(II) and Fe(III) are relatively low, limiting the activation efficiency of permonosulphate (PMS), resulting in poor removal of organic pollutants.

Method used

The iron-molybdenum bimetallic catalyst material (SLFP-MoS2) is generated by chemically combining waste lithium iron phosphate (SLFP-MoS2) to improve the activation efficiency of PMS.

Benefits of technology

The SLFP-MoS2 catalyst significantly improves the activity of PMS-based Fenton reaction, improves the efficiency of removing organic pollutants by 10.45 times, and the catalyst has good cycle stability and universality.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119612741A_ABST
    Figure CN119612741A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of solid waste recycling and organic wastewater treatment, and particularly relates to a method for treating organic wastewater by utilizing a composite material constructed by waste lithium iron phosphate to activate peroxymonosulfate. The method comprises the following steps: carrying out pyrolysis treatment on a waste lithium iron phosphate battery positive electrode material, and collecting a waste lithium iron phosphate SLFP powder material; preparing the SLFP into a uniform solution; sodium molybdate dihydrate and thioacetamide are added into the solution for a hydrothermal reaction, and a composite catalyst material SLFP-MoS2 is prepared; putting the catalyst into the wastewater to achieve adsorption equilibrium; and adding peroxymonosulfate to trigger an oxidation reaction, and removing organic pollutants in the solution. The SLFP-MoS2 catalyst provided by the invention can realize mutual promotion of Fe-Mo bimetal active sites, ensures stable circulation of iron ions and molybdenum ions in a local microenvironment, further activates peroxymonosulfate (PMS) to generate active species, and realizes effective removal of organic pollutants in wastewater.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of solid waste resource utilization and organic wastewater treatment, and specifically relates to a method for treating organic wastewater by activating peroxymonosulfate by constructing a composite material using waste lithium iron phosphate. Background Art

[0002] Driven by energy technology changes and medical and health policies, my country has gradually become a major producer and seller of lithium-ion batteries (LIBs). In recent years, the two major environmental issues of resource utilization of waste LIBs and organic wastewater pollution have attracted attention from all walks of life. The rational disposal of waste LIBs can not only alleviate the over-exploitation of global mineral resources, but also avoid the environmental hazards caused by improper disposal of waste LIBs; on the other hand, the effective treatment of organic wastewater is of great significance to ecosystem safety and human health. Advanced oxidation technology (AOPs) is one of the most popular and promising methods for treating organic wastewater. The hydroxyl radicals (•OH) produced by AOPs can convert organic pollutants into small molecular organic matter or directly oxidize them into CO2, H2O, etc. The activation conditions of permonosulfate (PMS) in AOPs are mild and easy to operate. The cleavage of the OO bond in PMS will trigger a chain reaction to generate various highly active substances to degrade pollutants. Iron-based compounds containing transition metal Fe have broad application prospects in PMS-based AOPs due to their low biological toxicity, environmental friendliness and easy access. However, the relatively low conversion rate of Fe(Ⅱ) and Fe(Ⅲ) limits the activation of PMS. Therefore, the improvement of PMS activation efficiency can be achieved by enhancing the conversion between Fe(Ⅱ) and Fe(Ⅲ). Molybdenum disulfide (MoS2) as a co-catalyst can accelerate the cycle of Fe(Ⅱ) and Fe(Ⅲ) to speed up the reaction rate. Therefore, the use of SLFP and MoS2 to construct a composite material to improve the activation efficiency of PMS and thus improve the degree of organic pollutant removal has important scientific significance in the fields of resource utilization of waste lithium batteries and efficient treatment of organic wastewater. Summary of the invention

[0003] The purpose of the present invention is to provide a method for treating organic wastewater by activating persulfate by constructing a composite material using waste lithium iron phosphate; the present invention provides a new resource-based approach for waste lithium iron phosphate SLFP positive electrode materials, based on the one-step composite formation of SLFP powder and molybdenum disulfide (MoS2) to effectively treat organic wastewater, thereby solving a pollution problem in wastewater. SLFP and MoS2 are chemically composited to achieve mutual promotion of Fe-Mo bimetallic active sites, ensure the stable circulation of iron ions and molybdenum ions within a local microenvironment, and then activate PMS to produce active species, thereby achieving effective removal of organic pollutants in wastewater; the addition of SLFP-MoS2 can greatly enhance the Fenton reaction activity of the PMS base class, and SLFP-MoS2+PMS is about 10.45 times that of the SLFP+PMS system; the SLFP-MoS2 catalyst has cyclic stability and universality, and has certain application prospects.

[0004] The technical problem solved by the present invention can be achieved by adopting the following technical solutions.

[0005] A method for utilizing waste lithium iron phosphate to construct a composite material to activate peroxymonosulfate to degrade organic wastewater comprises the following steps: S1. Dismantle the waste lithium iron phosphate battery, take out the positive electrode material, and collect the waste lithium iron phosphate SLFP powder after pyrolysis treatment; S2, placing waste lithium iron phosphate SLFP powder in ultrapure water and ultrasonically obtaining a uniform solution; S3, adding sodium molybdate dihydrate and thioacetamide to the solution obtained in step S2, stirring evenly to obtain a mixed solution; S4, transferring the mixed solution to a hydrothermal reactor for hydrothermal reaction to prepare a composite catalyst material SLFP-MoS2; S5, putting the composite catalyst material SLFP-MoS2 into the organic wastewater to achieve adsorption equilibrium; S6. Add peroxymonosulfate to trigger an oxidation reaction to remove organic pollutants from the solution.

[0006] Preferably, in step S1, pyrolysis is carried out under a nitrogen atmosphere, with a heating rate of 5-10 °C / min, a pyrolysis temperature of 150-800 °C, and a pyrolysis time of 2-16 h; further preferably, the heating rate is 8-10 °C / min, the pyrolysis temperature is 500-700 °C, and the pyrolysis time is 2-8 h; more preferably, the pyrolysis heating rate is 10 °C / min, the pyrolysis temperature is 600 °C, and the time is 2 h.

[0007] Preferably, in step S2, the mass ratio of SLFP to water is 1:1000-20:1000; further preferably, the mass ratio of SLFP to water is 10:1000.

[0008] Preferably, in step S3, the mass ratio of sodium molybdate dihydrate to thioacetamide is 2: 1-1: 2, the mass ratio of sodium molybdate dihydrate to water is 1: 1000-50: 1000, and the stirring method adopts a mechanical magnetic stirring method at a stirring rate of 100-1000 rpm; further preferably, the mass ratio of sodium molybdate (dihydrate), thioacetamide and water is 16: 25: 1000, and the stirring method adopts a mechanical magnetic stirring method at a stirring rate of 300 rpm.

[0009] Preferably, in step S4, the hydrothermal reaction temperature is 160-240 ℃, and the hydrothermal reaction time is 2-48 h; further preferably, the hydrothermal reaction temperature is 180-220 ℃, and the hydrothermal reaction time is 10-30 h; more preferably, the hydrothermal reaction temperature is 200 ℃, and the hydrothermal reaction time is 24 h; the composite catalyst material SLFP-MoS2 has a three-dimensional flower-like nanostructure.

[0010] Preferably, in step S5, in the wastewater treatment system, the initial concentration of organic pollutants is 1-1000 μmol / L, the initial pH value of the organic wastewater is between 2.0-12.0, the amount of catalyst added is 0.02-2 g / L, and the adsorption equilibrium time is 10-60 min; the pollutants in the organic wastewater include ciprofloxacin, bisphenol A, carbamazepine, tetracycline and sulfamethoxazole; in step S6, in the wastewater treatment system, the concentration of permonosulfate is 0.01-1.0 mM, the reaction time of adding permonosulfate is 3-30 min, and the reaction temperature is 25-35 °C. Further preferably, in step S5, in the wastewater treatment system, the initial concentration of organic pollutants is 1-50 μmol / L, the initial pH value of the organic wastewater is between 3.0-11.0, the amount of catalyst added to the system is 0.1-0.3 g / L, and the adsorption equilibrium time is 20-40 min; in step S6, the peroxymonosulfate concentration is 0.1-1.0 mmol / L; the reaction time of adding peroxymonosulfate is 3-15 min, and the reaction temperature is 25-30 °C.

[0011] More preferably, in step S5, the initial concentration of organic pollutants in the wastewater treatment system is 20 μM, the pH value of the wastewater is adjusted to 5.0, the amount of catalyst added to the system is 0.1 g / L, the concentration of permonosulfate in the solution is 0.5 mM, and the reaction time for adding permonosulfate is 15 min.

[0012] Compared with the prior art, the present invention has the following beneficial effects: 1. The addition of SLFP-MoS2 catalyst can greatly improve the activity of PMS-based Fenton reaction. The first-order kinetic constant of SLFP-MoS2+PMS system is 0.3836 min −1 , which is about 10.45 times that of the SLFP+PMS system.

[0013] 2. The SLFP-MoS2 catalyst has cyclic stability. From the experimental results, it can be seen that the degradation effect of the model organic pollutant ciprofloxacin in water after four cycles reached 100.0%, 98.69%, 96.94% and 95.38% respectively.

[0014] 3. SLFP-MoS2 catalyst is universal for different organic wastewaters, and the degradation rates of 20 μM bisphenol A, 20 μM carbamazepine, 20 μM tetracycline and 20 μM sulfamethoxazole can reach 92.75%, 98.45%, 100% and 100% respectively within 15 min. BRIEF DESCRIPTION OF THE DRAWINGS

[0015] Figure 1 This is a SEM characterization image of waste lithium iron phosphate (SLFP).

[0016] Figure 2 This is a SEM characterization image of the SLFP-MoS2 catalytic material constructed by the present invention.

[0017] Figure 3 These are the ciprofloxacin degradation curves of the SLFP-MoS2 catalytic material constructed by the present invention under different PMS concentration conditions and their corresponding first-order kinetic constants.

[0018] Figure 4 These are the ciprofloxacin degradation curves of the SLFP-MoS2 catalytic material constructed by the present invention under different catalyst dosage conditions and the first-order kinetic constants corresponding thereto.

[0019] Figure 5 The SLFP-MoS2 catalytic material constructed by the present invention is a ciprofloxacin degradation curve under different ciprofloxacin wastewater concentration conditions and the first-order kinetic constants corresponding to each of them.

[0020] Figure 6 The ciprofloxacin degradation curves of the SLFP-MoS2 catalytic material constructed by the present invention under different pH conditions and the first-order kinetic constants corresponding thereto.

[0021] Figure 7 It is the first-order kinetic fitting line of the degradation of ciprofloxacin under optimal conditions for the SLFP-MoS2 catalytic material and SLFP constructed by the present invention.

[0022] Figure 8 This is a cyclic experimental curve of the degradation of ciprofloxacin by the SLFP-MoS2 catalytic material constructed by the present invention.

[0023] Fig. 9 This is the degradation curve of the SLFP-MoS2 catalytic material constructed by the present invention for removing bisphenol A, carbamazepine, tetracycline and sulfamethoxazole under optimal conditions. DETAILED DESCRIPTION

[0024] In order to make the technical means, creative features, objectives and effects achieved by the present invention easy to understand, the present invention is further described below in conjunction with specific embodiments and drawings.

[0025] Example 1

[0026] A method for treating organic wastewater by using waste lithium iron phosphate to construct a composite material for activating peroxymonosulfate, wherein the composite material is prepared by the following steps: The waste lithium iron phosphate batteries were disassembled to obtain the positive electrode materials. After heat treatment, the waste lithium iron phosphate (SLFP) powder materials were collected and pyrolyzed in a nitrogen atmosphere with a heating rate of 10 ℃ / min, a pyrolysis temperature of 600 ℃, and a time of 2 h.

[0027] The SLFP powder was placed in ultrapure water and ultrasonically treated to obtain a uniform solution, and the mass ratio of SLFP to water was 10:1000.

[0028] Sodium molybdate (dihydrate) and thioacetamide are dissolved in the above solution, and magnetic stirring is performed to obtain a uniform mixed solution. The mass ratio of sodium molybdate (dihydrate), thioacetamide and water is 16:25:1000. The stirring method adopts mechanical magnetic stirring at a stirring rate of 300 rpm.

[0029] The above solution was transferred to a micro hydrothermal reactor and heated to react to prepare the composite catalyst material SLFP-MoS2; the heating reaction temperature was 200°C and the reaction time was 24 h.

[0030] SEM characterization of waste lithium iron phosphate positive electrode material (SLFP) Figure 1 As shown, SLFP is an olivine-type particle; the SEM characterization image of the composite catalytic material (SLFP-MoS2) of the present invention is as shown Figure 2 As shown, the SLFP-MoS2 composite material has a three-dimensional flower-like nanostructure.

[0031] Example 2

[0032] The present invention conducts relevant degradation experiments on the constructed composite material. The degradation experiment of the constructed composite material adopts a typical research method. Here, the composite material catalyst (SLFP-MoS2) is mainly used to activate peroxymonosulfate (PMS) to degrade the model organic pollutant ciprofloxacin (CIP) in water. The experimental process of degrading CIP by all SLFP-MoS2 catalysts is as follows: 1 mL of 5 mM CIP solution is added to 250 mL ultrapure water, and the pH of the system is adjusted to the experimental value with 0.1 M sodium hydroxide solution or 0.1 M sulfuric acid solution. When the magnetic thermostatic stirrer is continuously working, the temperature is set to 30°C, SLFP-MoS2 is added to the CIP solution and the timing is started. After 30 minutes, the adsorption and desorption equilibrium is reached, and 1 mL of PMS with a concentration of 0.125 M is added. The water sample is drawn every 3 minutes and filtered with a 0.22 μm polyethersulfone (PES) membrane until 15 minutes are completed, and the CIP concentration is determined by a high performance liquid chromatography (HPLC).

[0033] In order to further illustrate the effect of the present invention, the following is a comparison of different PMS concentrations, SLFP-MoS2 catalyst addition amounts, CIP concentrations and pH effects: 250 mL pure water, 20 μM CIP concentration, 0.1 mM, 0.2 mM, 0.5 mM, 0.8 mM and 1.0 mM PMS concentrations, 25 mg SLFP-MoS2 catalyst, pH = 5; 250 mL pure water, 20 μM CIP concentration, 0.5 mM PMS concentration, 0.025 g / L, 0.05 g / L, 0.10 g / L, 0.15 g / L and 0.20 g / L SLFP-MoS2 catalyst, respectively, pH = 5; 250 mL pure water, CIP concentrations of 10 μM, 15 μM, 20 μM, 25 μM and 30 μM, PMS concentration of 0.5 mM, SLFP-MoS2 catalyst of 25 mg, pH = 5; 250 mL pure water, 20 μM CIP concentration, 0.5 mM PMS concentration, 25 mg SLFP-MoS2 catalyst, pH = 3, 5, 7, 9 and 11; The experimental results are as follows: Figure 3 As shown in the results, the increase of PMS concentration in the system can enhance the degradation of CIP. When the PMS concentration is in the range of 0.1 mM to 0.5 mM, the degradation rate of CIP continues to increase, and its first-order kinetic constant (k obs )From 0.2952min −1 Improved to 0.3491 min −1The effect of catalyst dosage on degradation is as follows Figure 4 As shown in Figure 2, as the amount of SLFP-MoS2 increases from 0.025 g / L to 0.10 g / L, the removal rate is greatly improved, k obs From 0.0398 min −1 Increased to 0.3491 min −1 The higher the catalyst dosage, the higher the pollutant removal rate. Figure 5 The effect of CIP concentration (10, 15, 20, 25 and 30 μM) on the degradation effect is shown. When the CIP concentration increases from 10 μM to 30 μM, the degradation efficiency decreases from 100.0% to 91.8%, and the rate constant increases from 1.3493min −1 Down to 0.1228 min −1 Taking into account the economic benefits and degradation efficiency, the PMS concentration used in the subsequent study was 0.5 mM, the catalyst dosage was 0.10 g / L, and the CIP concentration was 20 μM. Figure 6 The effect of solution pH on CIP degradation is described. As the solution pH increases from 3 to 9, the removal rate decreases from 100.0% to 89.0%, k obs From 0.5192 min −1 Reduced to 0.1153min −1 . It shows that acidic conditions are more conducive to degradation than neutral and weak alkaline conditions in the SLFP-MoS2 / PMS system, but the degradation effect of CIP can also reach more than 95% by extending the reaction time under neutral or weak alkaline conditions to 30 min. At pH 11, because PMS can be strongly activated under strong alkaline conditions, the degradation of CIP is greatly accelerated. In summary, the SLFP-MoS2 / PMS system has a wide pH application range and avoids the treatment cost of additional pH changes caused by further water treatment processes.

[0034] Figure 7 The first-order kinetic fitting line of the degradation of ciprofloxacin under the optimal conditions of the SLFP-MoS2 catalytic material and SLFP constructed by the present invention is shown. Figure 7 It can be seen that the combination of SLFP and MoS2 can greatly improve the degradation rate of CIP. The first-order kinetic constant of the SLFP-MoS2+PMS system is 0.3836 min −1 , which is about 10.45 times that of the SLFP+PMS system.

[0035] The reusability and stability of the constructed SLFP-MoS2 catalytic material were also evaluated. Figure 8After four cycles, the removal rate of CIP still remained above 95%, which shows that the catalyst has good cycle stability and has certain application prospects.

[0036] Example 3

[0037] In order to further illustrate the effect of the present invention, the degradation effects of different organic pollutants are compared below: Bisphenol A (BPA) wastewater solution, carbamazepine (CMZ) wastewater solution, tetracycline (TC) wastewater solution, and sulfamethoxazole (SMX) wastewater solution were prepared. The organic pollutant concentration of the wastewater solution was 20 μM. The pH value of the wastewater was adjusted to 5.0, and the reaction temperature was 30°C.

[0038] The catalysts were added into 250 mL of prepared wastewater respectively, and the adsorption equilibrium was reached in 30 min. The added mass of SLFP-MoS2 catalyst was 25 mg.

[0039] Permonosulfate (PMS) was added to trigger the oxidation reaction to remove organic pollutants in the solution. The concentration of PMS in the solution was 0.5 mM.

[0040] Example 3 Experimental results are as follows Fig. 9 As shown, the results showed that the degradation rates of 20 μM BPA, 20 μM CMZ, 20 μM TC and 20 μM SMX by SLFP-MoS2 catalyst reached 92.75%, 98.45%, 100% and 100%, respectively, within 15 min.

[0041] The above shows and describes the basic principles and main features of the present invention and the advantages of the present invention. Those skilled in the art should understand that the present invention is not limited to the above embodiments. The above embodiments and descriptions are only for explaining the principles of the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, and these changes and improvements fall within the scope of the present invention to be protected. The scope of protection claimed in the present invention is defined by the attached claims and their equivalents. The purpose of the present invention is to provide a new resource-based approach for waste lithium iron phosphate positive electrode materials, based on the one-step composite generation of iron-molybdenum bimetallic catalyst materials from waste lithium iron phosphate powder and molybdenum disulfide, which is used to effectively treat organic wastewater and alleviate the current water pollution problem.

Claims

1. A method for treating organic wastewater by using waste lithium iron phosphate to construct a composite material to activate peroxymonosulfate, characterized in that: The steps include: S1. Dismantle the waste lithium iron phosphate battery, take out the positive electrode material, and collect the waste lithium iron phosphate SLFP powder after pyrolysis treatment; S2, placing waste lithium iron phosphate SLFP powder in ultrapure water and ultrasonically obtaining a uniform solution; S3, adding sodium molybdate dihydrate and thioacetamide to the solution obtained in step S2, stirring evenly to obtain a mixed solution; S4, transferring the mixed solution to a hydrothermal reactor for hydrothermal reaction to prepare a composite catalyst material SLFP-MoS2; S5, putting the composite catalyst material SLFP-MoS2 into the organic wastewater to achieve adsorption equilibrium; S6. Add peroxymonosulfate to trigger an oxidation reaction to remove organic pollutants from the solution.

2. The method according to claim 1, characterized in that: In step S1, the pyrolysis is carried out in a nitrogen atmosphere, with a heating rate of 5-10°C / min, a pyrolysis temperature of 150-800°C, and a pyrolysis time of 2-16 h.

3. The method according to claim 1, characterized in that: In step S2, the mass ratio of the waste lithium iron phosphate SLFP powder to water is 1:1000-20:1000.

4. The method according to claim 1, characterized in that: In step S3, the mass ratio of sodium molybdate dihydrate to thioacetamide is 2:1-1:2, the mass ratio of sodium molybdate dihydrate to water is 1:1000-50:1000, and the stirring method adopts mechanical magnetic stirring at a stirring rate of 100-1000 rpm.

5. The method according to claim 1, characterized in that: In step S4, the hydrothermal reaction temperature is 160-240° C., and the hydrothermal reaction time is 2-48 h; the composite catalyst material SLFP-MoS2 has a three-dimensional flower-like nanostructure.

6. The method according to claim 1, characterized in that: In step S5, in the wastewater treatment system, the initial concentration of organic pollutants in the organic wastewater is 1-1000 μmol / L, the initial pH value of the organic wastewater is between 2.0-12.0, the amount of catalyst added is 0.02-2 g / L, and the adsorption equilibrium time is 10-60 min.

7. The method according to claim 1, characterized in that In step S5, the organic pollutants in the organic wastewater include ciprofloxacin, bisphenol A, carbamazepine, tetracycline and sulfamethoxazole.

8. The method according to claim 1, characterized in that: In step S6, the concentration of permonosulfate in the wastewater system is 0.01-1.0 mmol / L; the reaction time of adding permonosulfate is 3-30 min, and the reaction temperature is 25-35°C.

9. The method according to claim 1, characterized in that: In step S5, in the wastewater treatment system, the initial concentration of organic pollutants is 1-50 μmol / L, the initial pH value of the organic wastewater is between 3.0-11.0, the amount of catalyst added to the system is 0.1-0.3 g / L, and the adsorption equilibrium time is 20-40 min; in step S6, the peroxymonosulfate concentration is 0.1-1.0 mmol / L; the reaction time of adding peroxymonosulfate is 3-15 min, and the reaction temperature is 25-30 °C.

Citation Information

Patent Citations

  • Method for catalytically degrading organic wastewater by adopting spent lithium-ion battery anode materials

    CN108147566A

  • Method for degrading organic dye in water by activating persulfate by using molybdenum disulfide synergized bivalent iron

    CN110227499A

  • Method for removing pollutants by synergistically catalyzing persulfate with molybdenum disulfide and ferric ions

    CN111003790A

  • Method for removing phenol by constructing composite material and activating peroxymonosulfate under neutral condition

    CN116282471A

  • Preparation method of iron-molybdenum bimetal MOF derivative catalyst and application of iron-molybdenum bimetal MOF derivative catalyst in wastewater treatment

    CN116943673A

Cited By

  • CO2 adsorbent and preparation method thereof

    CN120054445A